Public Excellent Service at Bapas Class II a Bojonegoro in Carrying out the Social Reintegration function - Aditya, Bima; Wulandari, Septi; Suhindarno, Heny (Jurnal Manajemen Pelayanan Publik, 2025)
This research is motivated by the high crime rate which has an impact on the large number of prisoners and former prisoners in Bojonegoro which causes prisons in the prison to exceed capacity. Bapas Kelas II A Bojonegoro applies (Prima Service) to achieve the function of social reintegration in order to provide guidance so that former prisoners do not have the potential to become recidivists which will increase the number of crime rates. This study aims to analyze the mental guidance services provided by Bapas in carrying out the function of social reintegration to reduce the crime rate. This study uses quantitative methods. The results showed that most service attributes have been running quite well, with many officer performance attributes in the good category (quadrant 2). The author argues that services at Bapas Bojonegoro have the potential to become a reference for inmate development services in correctional institutions, with an important note that the development of staff training and digitization of services must be prioritized to create good management for the supervision of former prisoners to improve and mentor mental well to achieve the function of social reintegration.